Human Heart Rhythms Synchronize While Co-sleeping - Yoon, Heenam; Choi, Sang Ho; Kim, Sang Kyong; Kwon, Hyun Bin; Oh, Seong Min; Choi, Jae-Won; Lee, Yu Jin; Jeong, Do-Un; Park, Kwang Suk (Frontiers in Physiology, 2019)
Human physiological systems have a major role in maintenance of internal stability. Previous studies have found that these systems are regulated by various types of interactions associated with physiological homeostasis. However, whether there is any interaction between these systems in different individuals is not well understood. The aim of this research was to determine whether or not there is any interaction between the physiological systems of independent individuals in an environment where they are connected with one another. We investigated the heart rhythms of co-sleeping individuals and found evidence that in co-sleepers, not only do independent heart rhythms appear in the same relative phase for prolonged periods, but also that their occurrence has a bidirectional causal relationship. Under controlled experimental conditions, the finding may be attributed to weak cardiac vibration delivered from one individual to the other via a mechanical bed connection. Our experimental approach could help in understanding how sharing behaviors or social relationships between individuals are associated with interactions of physiological systems.